2009
DOI: 10.1021/ja901685h
|View full text |Cite
|
Sign up to set email alerts
|

NMR Detected Hydrogen−Deuterium Exchange Reveals Differential Dynamics of Antibiotic- and Nucleotide-Bound Aminoglycoside Phosphotransferase 3′-IIIa

Abstract: In this work, hydrogen-deuterium exchange detected by NMR spectroscopy is used to determine the dynamic properties of the aminoglycoside phosphotransferase 3′-IIIa (APH), a protein of intense interest due to its involvement in conferring antibiotic resistance to both Gram negative and Gram positive microorganisms. This represents the first characterization of dynamic properties of an aminoglycosidemodifying enzyme. Herein we describe in vitro dynamics of apo, binary, and ternary complexes of APH with kanamycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 40 publications
3
36
0
Order By: Relevance
“…5 How APH achieves such a broad substrate selectivity is still not understood. As reported earlier by one of us, ligand-dependent changes in the dynamic behavior of APH were detected by NMR, hydrogen/deuterium (H/D) exchange experiments, 6 and isothermal titration calorimetry (ITC), 7 and gave insights into the mechanism of the substrate promiscuity of APH. While aminoglycoside binding to the apoenzyme induces an enhanced conformational stability of APH and a reduction of entropy, the enthalpic change upon aminoglycoside binding to the nucleotide-APH complex is about 20 kcal mol − 1 less negative, which is compensated for by a smaller entropic penalty.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…5 How APH achieves such a broad substrate selectivity is still not understood. As reported earlier by one of us, ligand-dependent changes in the dynamic behavior of APH were detected by NMR, hydrogen/deuterium (H/D) exchange experiments, 6 and isothermal titration calorimetry (ITC), 7 and gave insights into the mechanism of the substrate promiscuity of APH. While aminoglycoside binding to the apoenzyme induces an enhanced conformational stability of APH and a reduction of entropy, the enthalpic change upon aminoglycoside binding to the nucleotide-APH complex is about 20 kcal mol − 1 less negative, which is compensated for by a smaller entropic penalty.…”
Section: Introductionmentioning
confidence: 83%
“…Generally, it is assumed that ligand binding leads to reduced H/D exchange due to steric exclusion of solvent. 30,31 The surprising experimental observation that nucleotide binding destabilizes β-sheet residues 6 contradicts this idea and leads to the identification of dynamic protein domains. On the other hand, the calculation of theoretical Bfactors affirms that residue flexibility decreases with the number of closest neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…The most dramatic spectral differences were observed between the HSQC spectra of the apo-enzyme and the enzyme-aminoglycoside complexes. The HSQC spectrum of apo-APH shows a narrow dispersion and large resonance overlap indicating that the apo-form of the enzyme is very flexible in solution and/or may have intrinsically unstructured sections (Norris and Serpersu 2009). Even with the exclusion of the most crowded central part of the HSQC spectrum (Fig.…”
Section: Methods and Experimentsmentioning
confidence: 99%
“…Recent work from our laboratory suggested that this enzyme is very flexible in solution and the native apoenzyme exchanges all amide protons within *15 h of exposure to D 2 O while [40% is protected in enzymeaminoglycoside complexes even after 95 h of exposure (Norris and Serpersu 2009). Such flexibility allows this protein to recognize the solvent structure of aminoglycoside ligands and adopts its conformation to render the binding of a large number of aminoglycosides thermodynamically favorable (Ö zen et al 2008).…”
Section: Biological Contextmentioning
confidence: 99%
“…However, it should be pointed out that structural disorder in enzymes does occur 19 and has been linked to a wider substrate specificity. 20 Because of their widespread role in regulation, IDPs are, somewhat counterintuitively, often involved in protein binding and molecular recognition. In order to achieve recognition of a specific partner molecule, IDPs typically undergo a disorder-order transition upon contacting a target.…”
Section: Wallinmentioning
confidence: 99%